DESIGN AND IMPLEMENTATION DIARRHEAL SURVEILANCE REPORT INFORMATION SYSTEM WITH WATERFALL METHOD IN HEALTH DEVELOPMENT OF JEMBER - Lena Mastuti; Rinda Nurul K; Dony Setiawan HP (UPT Penerbitan Universitas Jember)
Epidemiological surveillance is process of datacollection analytical system to disease or healthproblems. Prevention efforts require a supportprogram surveillance system in district or city,provincial and national (Departemen Kesehatan RI,2003).A preliminary survey that researchers, that thereporting process surveillance in healthdevelopment of Jember is manually. Surveillanceofficers have to one by one monthly report dataevery puskesmas, so record the accuracy andcompleteness takes a long time.Design of website helps in sending data diarrhealsurveillance reporting to health development ofJember. Web-based data transmission areconfidential, because the data is stored in the formof a database, the delivery process faster andaccessed online at any time.Based on description above, researchers doresearch with title “Design and ImplementationDiarrheal Surveilance Report Information Systemwith Waterfall Method in Health Development ofJember”.